Assessment of Dairy Product Safety Supervision in Sales Link: A Fuzzy-ANP Comprehensive Evaluation Method - Tingqiang Chen; Shuaibin Wang; Lei Pei; Jining Wang (Journal of Food Quality)
An evaluation index system is developed to assess food safety supervision in the sales links of dairy products. Evaluation research is conducted using the fuzzy-ANP comprehensive evaluation model to assess the product safety supervision of dairy products in the sales link based on 307,705 survey data acquired from 1,501 online and offline dairy businesses in China. Evaluation results show that (1) the overall situation of dairy product safety supervision in the sales link is encumbered by the fact that the online situation of dairy product safety supervision in the sales link is general. It does not achieve a relatively good level; (2) the investment in food safety supervision of dairy products in the sales link is insufficient for the online e-commerce platforms. Especially, the processes of reviewing and approving relevant business sales qualification must be improved; (3) online business types do not directly determine the situation of dairy product safety supervision in the sales link, but the operating environment, sales staff quality, and warehousing management are common regulatory weaknesses; and (4) for offline provinces, the level of economic development can affect the situation of dairy product safety supervision in the sales link. Aside from emphasizing sales qualifications, economically backward provinces should improve the supervision of the operating environment, sales equipment, sanitary status of workers, and other aspects.